Occurrence of Babesia and Anaplasma in ruminants from the Catimbau National Park, Semiarid Region of Northeast Brazil - Moura, Liliane Moreira Donato; Farias, Ila Ferreira; de Sá, João Claudio Bezerra; da Silva e Souza, Dênisson; Santos, Paula Talita Torres; Freschi, Carla Roberta; de Oliveira, Jaqueline Bianque; Moraes-Filho, Jonas; Machado, Rosangela Zacarias [UNESP]; de Azevedo, Sergio Santos; Horta, Mauricio Claudio (My University, 2024)
Babesiosis and Anaplasmosis are diseases associated with economic losses; ticks and blood-sucking flies are important zoonotic vectors and reservoirs. This study aimed to investigate the presence of anti-Babesia spp. and anti-Anaplasma marginale antibodies using enzyme-linked immunosorbent assay (ELISA), in ruminants at the Catimbau National Park. Blood samples were collected from 119 sheep, 119 goats, and 47 cattle. Rhipicephalus microplus ticks were collected from cattle. ELISA showed seropositivity of 34% (16/47), 20.3% (24/119), and 16% (19/119) for anti-Babesia bovis; 34% (16/47), 15.2% (18/119), and 9% (7/119) for anti-Babesia bigemina; and 34% (16/47), 35.6% (42/119), and 17% (20/119) for anti-A. marginale antibodies in cattle, goats, and sheep, respectively. The information collected using an epidemiological questionnaire showed that mostly are breed in a semi-intensive system, with access to Caatinga vegetation. The circulation of B. bovis, B. bigemina, and A. marginale was confirmed. Thus, based on the prevalence, this suggests this is an enzootic instability area and is prone to outbreaks.
Ocorrência de Babesia e Anaplasma em ruminantes no Parque Nacional do Catimbau, região semiárida do Nordeste do Brasil
Keywords: Conservation unit; epidemiology; hemoparasites; ruminants; ticks